Shengmai Injection Suppresses Angiotensin II-Induced Cardiomyocyte Hypertrophy and Apoptosis via Activation of the AMPK Signaling Pathway Through Energy-Dependent Mechanisms - Li, Yiping; Ruan, Xiaofen; Xu, Xiaowen; Li, Cha; Qiang, Tingting; Zhou, Hua; Gao, Junjie; Wang, Xiaolong (Frontiers in Pharmacology, 2019)
Shengmai injection (SMI), a traditional Chinese herbal medicine extracted from Panax ginseng C.A. Mey., Ophiopogon japonicus (Thunb.) Ker Gawl., and Schisandra chinensis (Turcz.) Baill., has been used to treat acute and chronic heart failure. This study aimed to further clarify the effects of SMI on energy metabolism. SMI could improve the cell-survival rate and also reduce myocardial cell hypertrophy and apoptosis. Mitochondria are important sites of cellular energy metabolism, and SMI protects mitochondrial function, which was evaluated by mitochondrial ultrastructure, mitochondrial respiratory control ratio, and mitochondrial membrane potential (ΔΨm) in this study. The expression levels of adenosine triphosphate (ATP), adenosine triphosphate, and phosphocreatine (PCr) increased. The expression levels of free fatty acid oxidation [carnitine palmitoyltransferase-1 (CPT-1)], glucose oxidation [glucose transporter-4 (GLUT-4)], and mitochondrial biogenesis-related genes [peroxisome proliferator-activated receptor-γ coactivator-1α (PGC-1α)] were upregulated after SMI treatment. Adenosine monophosphate–activated protein kinase (AMPK) is an important signaling pathway regulating energy metabolism, and also can regulate the aforementioned indicators. In the present study, SMI was found to promote the phosphorylation of AMPK. However, the effects of SMI on fatty acid metabolism, glucose oxidation, mitochondrial biogenesis, and apoptosis of hypertrophic cardiomyocytes were partly blocked by AMPK inhibitor compound C. Moreover, decreased myocardial hypertrophy and apoptosis treated by SMI were inhibited by AMPK knockdown with shAMPK to a certain degree, and AMPK knockdown almost abolished the SMI-induced increase in the expression of GLUT-4, CPT-1, and PGC-1α. These data suggested that SMI suppressed Ang II-induced cardiomyocyte hypertrophy and apoptosis via the activation of the AMPK signaling pathway through energy-dependent mechanisms.